Cicero and the rise of deification at Rome - Cole, Spencer (Cambridge ; New York : Cambridge University Press, 2013)
"This book tells a part of the back-story to major religious transformations emerging from the tumult of the late Republic. It considers the dynamic interplay of Cicero's approximations of mortals and immortals with a range of artifacts and activities that were collectively closing the divide between humans and gods. A guiding principle is that a major cultural player like Cicero had a normative function in religious dialogues that could legitimize incipient ideas like deification. Applying contemporary metaphor theory, it analyzes the strategies and priorities configuring Cicero's divinizing encomia of Roman dynasts like Pompey, Caesar and Octavian. It also examines Cicero's explorations of apotheosis and immortality in the De re publica and Tusculan Disputations as well as his attempts to deify his daughter Tullia. In this book, Professor Cole transforms our understanding not only of the backgrounds to ruler worship but also of changing conceptions of death and the afterlife"--
Machine generated contents note: Introduction; 1. The cultural work of metaphor; 2. Experiments and invented traditions; 3. Charting the posthumous path; 4. Revisions and Rome's new god; Conclusions.
Description based on print version record.
Keywords: Apotheosis -- Rome; Emperor worship -- Rome; Cicero, Marcus Tullius; HISTORY / Ancient / General; BODY, MIND & SPIRIT / Spirituality / Paganism & Neo-Paganism; RELIGION / Antiquities & Archaeology; Electronic books